(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kyrykylytsia V. V. Experimental research of activation of students’ knowledge and cognitive activity in the process of working with dictionaries. In the article levels of criteria formation of students’ knowledge and cognitive activities activation in the process of working with dictionaries are defined on the basis of the experimental research analysis.